Ambientes fluviais laterais na bacia do Rio da Prata: Efeitos dos barramentos de hidrelétricas e da eutrofização - Júnior, José Roberto Debastiani [UNESP]; Naliato, Danilo Augusto de Oliveira [UNESP]; Perbiche-Neves, Gilmar; Nogueira, Marcos Gomes [UNESP] (FapUNIFESP (SciELO), 2016)
Aim: Identify large-scale limnological patterns in lateral water bodies of Río de La Plata Basin, considering the influence of river damming and urban conglomerates. Methods: Samplings were performed in a broad spatial scale (along 16 latitude degrees) during two seasonal periods (23 sites in summer and 20 sites in winter) for measurements of physical and chemical variables, chlorophyll a and periphyton biomass. Results: Geographical distance between sites was significantly correlated with the environmental dissimilarity (Euclidean distance). Reservoir and floodplain associated sites exhibited lower phosphorus concentration. Eutrophic conditions were higher in sites close to urban areas and regions with intensive agriculture and livestock activities, which exhibited higher conductivity, concentration of nitrogen and chlorophyll a. Sites associated to reservoirs had higher periphyton biomass. Inorganic suspended matter was higher in summer whereas organic suspended matter was higher in the winter, due to contrasting rain seasonality in the upper Paraná River sub‑basin. No significant correlation between the dissimilarity of the vegetation and the environmental dissimilarity or geographical distance between sites was observed. Conclusions: The limnological conditions in the fluvial lateral habitats in the Río de La Plata basin are highly influenced by reservoirs construction, intensive urban occupation and rain seasonality.
Fluvial lateral environments in río de La plata basin: Effects of hydropower damming and Eutrophication
Keywords: Human impact; Limnological variables; River dams; Water quality; Wetland